Identification of Teachers Professional Needs about Content Matter Knowledge at Primary School Level: A Way Forward to SDG-4 (Journal of Asian Development Studies, 2025)
The main objective of the study is to identify the primary school teachers' professional needs and guidelines for continuous professional development, and to identify the factors affecting teachers' professional development. The quantitative as well as qualitative (QUAN-qual) method was adopted. The explanatory sequential technique was used. The population of the study comprised all head teachers of primary schools in the district of Rahim Yar Khan, all primary school teachers serving in urban and rural areas of the district of Rahim Yar Khan. The simple random sampling was adopted for the study. The sample of the study comprised sixty-four (64) head teachers of primary schools in the district of Rahim Yar Khan. The three hundred and twenty 320 (64*5) primary school teachers in the district of Rahim Yar Khan. The population of the study comprised the Punjab province. Punjab province was divided into three clusters: Cluster-1: North Punjab, Cluster-2: Central Punjab, Cluster-3: South Punjab. The Cluster-3 South Punjab was divided into three divisions: Multan Division, Dera Gazi Khan Division, and Bahawalpur Division. The 16 head teachers and 80 primary school teachers serving in primary schools of Tehsil Sadiqabad, 16 head teachers and 80 primary school teachers serving in primary schools of Tehsil Rahim Yar Khan, and 16 head teachers and 80 primary school teachers serving in primary schools of Tehsil Khanpur. 16 head teachers and 80 primary school teachers serving in the primary schools of Tehsil Liaqatpur. The total sample comprised 64 head teachers and 320 primary school teachers with the same ratio of Gender and Locality. The collected data were analyzed using relevant statistical formulas, such as frequency, percentage, standard deviation, and mean score. The study showed that the mean value of males is 4.3565 and females is 4.3634, which reflects that females perform better than males. The standard deviation is 0.3820, t-value 0.363, df 437.509, and significance 0.722 also supported.